Family control and financing decisions - Ettore Crocci; John A. Doukas; Halit Gonenc (TÜSİAD-Koç University Economic Research Forum, 2010)
Empirical studies examining the financing decisions of the firm focus exclusively on publicly held firms, not family-controlled firms despite their economic importance. This study investigates the external financing behavior of family-controlled firms, using a comprehensive sample of 777 large European firms during the period 1998 to 2008. We document that, unlike nonfamily-controlled firms, the external financing decisions of family-controlled firms are influenced by control incentives and information asymmetry considerations. We find that family firms have a strong preference for debt financing, a noncontrol diluting security, while they are more reluctant to raise capital through equity offerings in comparison to nonfamily firms. We also find that credit markets, view family firms as more risk-averse and that family firms invest more in low-risk (fixed-asset capital expenditures (CAPEX)), than in high-risk investments (R&D expenditures) confirming their non-risk seeking behavior.
Keywords: G32; 330; family firms; financing decisions; equity issues; debt issues; capital structure; Familienunternehmen; Unternehmensfinanzierung; Kapitalstruktur; Europa